Increasing the Separation Capacity of Intact Histone Proteoforms Chromatography Coupling Online Weak Cation Exchange-HILIC to Reversed Phase LC UVPD-HRMS - Gargano, Andrea F. G. (J Proteome Res, 2018)
[Image: see text] Top-down proteomics is an emerging analytical strategy to characterize combinatorial protein post-translational modifications (PTMs). However, sample complexity and small mass differences between chemically closely related proteoforms often limit the resolution attainable by separations employing a single liquid chromatographic (LC) principle. In particular, for ultramodified proteins like histones, extensive and time-consuming fractionation is needed to achieve deep proteoform coverage. Herein, we present the first online nanoflow comprehensive two-dimensional liquid chromatography (nLC×LC) platform top-down mass spectrometry analysis of histone proteoforms. The described two-dimensional LC system combines weak cation exchange chromatography under hydrophilic interaction LC conditions (i.e., charge- and hydrophilicity-based separation) with reversed phase liquid chromatography (i.e., hydrophobicity-based separation). The two independent chemical selectivities were run at nanoflows (300 nL/min) and coupled online with high-resolution mass spectrometry employing ultraviolet photodissociation (UVPD-HRMS). The nLC×LC workflow increased the number of intact protein masses observable relative to one-dimensional approaches and allowed characterization of hundreds of proteoforms starting from limited sample quantities (∼1.5 μg).